2013
DOI: 10.1097/qad.0b013e328361fa4a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of carbosilane dendrimers in combination with maraviroc against HIV in vitro

Abstract: The evaluated two-drug combinations increase their antiviral potency supporting further clinical investigations to develop combinatorial formulated topical microbicides to fight against the worldwide HIV spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…8,9,14,15 Eight dendrimers were dissolved in distilled water in a final concentration of 1 mM. Dilutions to µM range were generated in distilled water from the stock.…”
Section: Materials and Methods Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,14,15 Eight dendrimers were dissolved in distilled water in a final concentration of 1 mM. Dilutions to µM range were generated in distilled water from the stock.…”
Section: Materials and Methods Compoundsmentioning
confidence: 99%
“…14,38 To potentially limit the selection of resistant strains that may compromise the treatment options and improve the efficacy of current antivirals, the use of combinations of different agents could be an interesting approach. 8,9,14,17 Our dendrimers have shown an additive or synergistic profile when combined with ACV or TFV. The obtained synergy can be due to the fact that the dendrimers and ACV or TFV act at different steps in the viral cycle.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…26 The TZM-bl cells were cultured as described. 25 Peripheral blood mononuclear cells (PBMCs) were isolated using a standard Ficoll gradient from buffy coats (Rafer, Spain) and were cultured as previously described. …”
Section: Materials and Methods Cells And Cell Culturementioning
confidence: 99%
“…24 Moreover, we have already shown that combination of maraviroc and the polyanionic carbosilane dendrimers G3-S16 and G2-NF16 increased their antiviral potency, both additively and synergistically, against CCR5-tropic HIV; the main viral strain involved in primary infection during sexual transmission, and dual tropic HIV-1 isolates. 25 In this work, we studied the combinatorial activity profile of these polyanionic carbosilane dendrimers (G3-S16 and G2-NF16; Figure 1) in combination with other ARVs, such as zidovudine (AZT), efavirenz (EFV), and TFV, International Journal of Nanomedicine 2014:9 submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%